Developing a Standard Set of Patient-Centred Outcomes for Inflammatory Bowel Disease—an International, Cross-disciplinary Consensus. (5th December 2017) - Kim, Andrew H; Roberts, Charlotte; Feagan, Brian G; Banerjee, Rupa; Bemelman, Willem; Bodger, Keith; Derieppe, Marc; Dignass, Axel; Driscoll, Richard; Fitzpatrick, Ray; Gaarentstroom-Lunt, Janette; Higgins, Peter D; et al.
Abstract: Background and Aims: Success in delivering value-based healthcare involves measuring outcomes that matter most to patients. Our aim was to develop a minimum Standard Set of patient-centred outcome measures for inflammatory bowel disease [IBD], for use in different healthcare settings. Methods: An international working group [ n = 25] representing patients, patient associations, gastroenterologists, surgeons, specialist nurses, IBD registries and patient-reported outcome measure [PROM] methodologists participated in a series of teleconferences incorporating a modified Delphi process. Systematic review of existing literature, registry data, patient focus groups and open review periods were used to reach consensus on a minimum set of standard outcome measures and risk adjustment variables. Similar methodology has been used in 21 other disease areas [www.ichom.org ]. Results: A minimum Standard Set of outcomes was developed for patients [aged ≥16] with IBD. Outcome domains included survival and disease control [survival, disease activity/remission, colorectal cancer, anaemia], disutility of care [treatment-related complications], healthcare utilization [IBD-related admissions, emergency room visits] and patient-reported outcomes [including quality of life, nutritional status and impact of fistulae] measured at baseline and at 6 or 12 month intervals. A single PROM [IBD-Control questionnaire] was recommended in the Standard Set and minimum risk adjustment data collected at baseline and annually were included: demographics, basic clinical information and treatment factors. Conclusions: A Standard Set of outcome measures for IBD has been developed based on evidence, patient input and specialist consensus. It provides an international template for meaningful, comparable and easy-to-interpret measures as a step towards achieving value-based healthcare in IBD.